Changes in the Biomechanical Properties of Corneal Stromal Lens after Collagen Crosslinking Induced by EDC-NHS - Rong Shi; Lijing Wang; Chengpeng Liang; Yu Cheng; Tai Xiang Liu; Xin Luo (Journal of Ophthalmology)
Introduction. To evaluate the changes of lens antidilatation, antiedema, and antienzymolysis ability after different concentrations of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide (EDC-NHS)-induced collagen cross-linking. Methods. Corneal stromal lenticules (n = 100) obtained from small incision lenticule extraction (SMILE) procedures were divided into 5 groups: no treatment (control); EDC/NHS (5%/2.5%); EDC/NHS(5%/5%); EDC/NHS (10%/5%); riboflavin and ultraviolet-A light (UVA). Collagen crosslinking was induced using EDC-NHS and UVA. Biomechanical assessments including inflation test, enzymatic degradation resistance, and light transmittance were evaluated posttreatment. Results. (1) Lenticule apex displacement ranked: control Group > UVA Group > Group (5%/5%) > Group (5%/2.5%) > Group (10%/5%) (Friedman test, p<0.0001). (2) Light transmittance was significantly higher in the crosslinked groups versus control, with EDC/NHS superior to UVA riboflavin. After 15 minutes in PBS, light transmittance decreased due to swelling; however, crosslinked groups maintained significantly higher transmittance versus control. (3) Following crosslinking, enzymatic resistance improved significantly, with the EDC-NHS crosslinking group was significantly better than the UVA cross-linking group. Conclusions. EDC/NHS crosslinking enhanced lenticule stiffness, antiedema, and enzymatic resistance and without compromising the transparency of the lens. Moreover, EDC/NHS crosslinking efficacy exceeded UVA riboflavin crosslinking in improving lenticule biomechanical properties.